A room of our own? How integrity administrators inhabit and collaborate across third space - Greer Murphy; Emily Perkins (Journal of Learning Development in Higher Education)
Academic honesty and integrity (AH/AI) are claimed to be a fundamental set of values and practices that can facilitate students’ success in higher education and that remains essential to the development of ethical citizenship after graduation. Despite broad rhetoric about integrity being critical to higher education’s mission, not much is known about where this work resides within institutions or who, specifically, carries it out. Reporting on semi-structured interviews with 11 integrity administrators, our case study offers insight to the similarities between integrity and other third space labour, focusing on how administrators conceptualise and pursue collaboration—or not—as part of their roles. By describing the power imbalances and overall lack of organisational structure in which integrity administrators operate, as well as the absence of trust and credibility with which they contend, our study highlights lived experiences and working struggles of an under-recognised subset of third space laborers. It suggests that integrated practice and career longevity will remain impossible unless there are fundamental sea changes in institutional understanding, attention, and support.